PERKEMBANGAN KERAJAAN ALLAH ZAMAN PAULUS: PAULUS DI ATHENA (KIS. 17:16-34) - Isa Andreyanku Lana; Lien Meilan, Imelda Rosen, Sarmauli (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study analyzes the evangelistic strategy of the Apostle Paul in the city of Athens, as recorded in Acts 17:16-34, focusing on the spread of the Kingdom of God among a society rich in philosophical heritage and religious diversity. Athens, as the intellectual center of the world at that time, presented significant challenges for Paul in conveying the message of Jesus Christ's resurrection. This study employs a qualitative approach to analyze the historical context, biblical text, and related literature. The findings show that Paul used a clever strategy by linking the message of the Kingdom of God to local religious elements, such as the altar to an unknown god. He also engaged in dialogue with philosophers and community leaders, using language and arguments relevant to Greek philosophical thought. Paul's teachings challenged the traditional beliefs of Athenian society regarding idol worship and introduced the concept of a universal God and fundamental spiritual values. The reaction of the Athenians was mixed; some mocked the idea of resurrection, while others, such as Dionysius and Damaris, accepted and believed. Paul's strategy highlights the importance of adaptation, openness, and dialogue in conveying religious messages in pluralistic settings. Love, tolerance, and steadfast faith were identified as key to facing challenges and expanding the influence of the Kingdom of God. This study concludes that despite rejection, success in reaching diverse societies can be achieved through wise and adaptive approaches.